An analysis on a strategic asset allocation: a case study on CIMB Wealth Advisors (CWA) conventional fund / Nurull Rashidah Ahmad Abzan - Ahmad Abzan, Nurull Rashidah (2011)
This study explores the relationship between asset allocations of Local Equity versus Regional Equity (CPECPAE), Local Equity versus Global Equity (CPECPGG), Local Equity versus Fixed Income (CPECPSB), Regional Equity versus Global Equity (CPAECPGG), and Regional Equity versus Fixed Income (CPAECPSB) with the return of portfolio. Asset allocation is based on the idea that in different years a different asset is the best performing one. Therefore, this study is important to investigate whether different asset allocation can produce different return of portfolio and with combination of assets can maximizes return of portfolio with suitable risk. The data used are from secondary data and have been calculated into monthly return of each fund. Then, the collected data is being run using SPSS. Once the results have been derived from the program, then the results is interpreted by a number of statistical. In this study, the results are interpreted by using Multiple Linear Regressions, Coefficient of Determination (R2), T-statistic and F-statistic. In conclusion, based on the result interpreted using Multiple Linear Regressions, Coefficient of Determination (R₂), T-statistic and F-statistic, asset allocations of CPECPAE and CPECPGG have significant (positive) relationship with return on portfolio, while the asset allocations of CPECPSB, CPAECPGG and CPAECPSB show insignificant (negative) relationship with return of portfolio. In the end of this research, the researcher has made some recommendations for the investors and for the further researchers